Prostate carcinoma mimicking a sphenoid wing meningioma. (2015) - Bradley, Lucas H.; Burton, Matthew; Gokden, Murat; Serletis, Demitre
Highlights: Meningiomas and metastatic dural-based tumors share common imaging features. We present a rare case of sphenoid wing prostate metastasis resembling meningioma. Dural-based lesions in the elderly require work-up to rule out metastasis. Identification of widespread metastases favors palliation, in certain cases. Abstract: Introduction: We report here on a rare case of a large, lateral sphenoid wing tumor with radiographic and intraoperative findings highly suggestive of meningioma, yet pathology was in fact consistent with metastatic prostate adenocarcinoma. Presentation of case: An 81 year-old male presented with expressive dysphasia, right-sided weakness and headaches. Imaging revealed a heterogeneously-enhancing lesion based on the left lateral sphenoid wing. The presumed diagnosis was strongly in favor of meningioma, and the patient underwent complete resection of the dural-based lesion. Final pathology confirmed the unexpected finding of a metastatic prostate adenocarcinoma. Although he tolerated surgery well, the patient was subsequently referred for palliative therapy given findings of widespread systemic disease. Discussion: Intracranial metastases may involve the dura, at times presenting with rare radiographic features highly suggestive for meningioma, as in our case here. This makes differentiation, at least based on imaging, a challenge. Elderly patients presenting with neurological deficits secondary to a newly-diagnosed, dural-based lesion should thus be considered for metastasis, prompting additional imaging studies (including body CT, MRI or PET) to rule out a primary lesion elsewhere. In some cases, this may affect the overall decision to proceed with surgical resection, or alternatively, to proceed directly to palliative therapy (the latter decision made in the context of widespread metastatic disease). Conclusion: We conclude that dural-based metastatic lesions may mimic meningiomas, warranting thorough pre-operative work-up to exclude the possibility of metastasis. In certain cases, identification of widespread disease might preclude surgery and favor palliation, instead.